Pro Oracle application express - Scott, John Edward (Expert's voice in Oracle., 2008)
Application Express, or APEX, is one of the most innovative products to come out of Oracle in years. APEX is an application development framework for developing database backed applications. It s easy enough to get started in that power users can quit storing data in random spreadsheets and instead centralize their data in the powerful Oracle database, all without developer help. Developers arent left out, however. Those who choose to can go deep and leverage the full power and flexibility of Oracles database engine. Getting started with APEX is easy. Learning how to take full advantage of APEX is the problem. It was the problem, that is, until this book came along. In Pro Oracle Application Express, authors John Scott and Scott Spendolini open the hood of APEX and expose the full power behind its easy to use GUI interface. They show you what you need to know to produce powerful, professionally polished applications, things such as user-authentication models, approaches to layout and navigation, how to integrate Ajax, how to deal with localization issues such as time zones and translations, how to customize the look and feel of an APEX web site, and much, much more. The authors are well qualified to write on APEX. John Scott runs ShellPrompt, a hosting service that handles many large-scale APEX applications, some of which he is paid to develop. John is a hard core APEX developer. His coauthor, Scott Spendolini, is one of the original creators of APEX. Both John and Scott now base their fulltime careers on developing APEX applications. Pro Oracle APEX is your opportunity to learn APEX from the very best.